Could this be a Win Win Opportunity - Butler, Ulda (2010)
It is generally agreed that the identification of entrepreneurial opportunities plays a significant role in creating employment and wealth in the economy. Although a considerable amount of research has been undertaken in the private sector little has been done in the social care market to identify entrepreneurial opportunities. In response this study explores the identification of entrepreneurial opportunities through semi structured interviews and secondary data in relation to the over and under 65s. The analysis shows that potential entrepreneurial opportunities exist, to provide an integrated service, which combines information, management of personal assistants, and planning for future care needs. However further work is needed to explore the potential in greater detail to determine viability and profitability.